Operational Procedures for Ship Arrival & Departure Services for KM. Dharma Kencana V Customer Satisfaction at Donggala Port - Yakin, Ainul; Setiono, Beni Agus; Saputra, Toto Dwijaya (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
: This study describes the operational procedures for the arrival and departure of the KM. Dharma Kencana V at Donggala Port and evaluates their impact on passenger satisfaction. This port is crucial for connectivity in Central Sulawesi, so the effectiveness of operational procedures is crucial. Using a qualitative approach with observation, interviews, and documentation, the results show that procedures such as berthing, embarkation, disembarkation, and vehicle loading are in accordance with standards, although there are obstacles such as schedule delays and suboptimal services for passengers with special needs. In general, passenger satisfaction is good, but improvements are needed in terms of punctuality and comfort. Recommendations are provided for operators and port authorities to improve coordination and service quality for more effective and user-friendly maritime transportation.